Developing HALM Teaching Competencies in PETE Teacher Candidates. Issue 5 (13th June 2018) - Wilkinson, Carol; Prusak, Keven; Zanandrea, Maria
Abstract : The lifetime activities approach, which grew out of the lifetime physical activity model, has informed the practice of one physical education teacher education (PETE) program as it prepares teacher candidates to teach K–12 students about the importance of health, health-related fitness, and physical activity. Health-enhancing behaviors such as healthy eating habits, using stress management techniques, and healthy sleep behaviors are also introduced to students. This article describes activities that are presented to help PETE teacher candidates develop healthy and active lifestyle management (HALM) teaching competencies. Two HALM teaching competencies (one-minute HALM tips and object lessons) are defined, and a description of where they appear in the curriculum and how they are assessed after field teaching of K–12 students is provided.